(untitled) (Educational Dimension, 2022)
This paper is about people’s strategic behavior as observed through experiments. The research question posed in this paper is how players (primarily children) learn in complex strategic situations that they have never encountered before. We examine data from various games played during popular game theory lectures and present findings about players’ strategic learning progress while competing with other players. Four "pick a number" games with similar-looking rules but very different properties were investigated. These games were presented to various groups of listeners. The collected data is available for replication and analysis in an open repository. In this paper, we analyze data and propose an agent-based model of a beauty pageant game to explain observed behavior. Finally, we discuss the findings, hypotheses to test, and open questions for future research.